Zoning strategies for ecological restoration in the karst region of Guangdong province, China: a perspective from the “social-ecological system” - Liu, Yang; Huang, Jiajun; Lin, Wei (Frontiers in Environmental Science, 2024)
Ecological restoration holds great significance in addressing environmental degradation and rock desertification in karst areas. Zoning strategy is a fundamental task in understanding the interrelationship between human-environment to foster sustainable development. We explore "socialecological" system and conduct a case study on the karst region in Guangdong Province, China. An evaluation framework consists of "development pressure", "sensitivity status", and "resilience potential" was established. The results show that: regions with high pressure of development are predominantly located in high-density urban areas. The generally distribution of the comprehensive status index exhibits significant spatial heterogeneity. Regions with low sensitivity are found on the eastern and western sides of the study area. The comprehensive resilience values are largely influenced by per capita energy-saving and environmental protection expenditures. The restoration zones mainly concentrated in the contiguous regions of the northwestern and southern parts, covering more than half of the total area. The conservation zones are more numerous and primarily situated in the northern and eastern parts. By integrating socio-economic and ecological factors, this study proposes ecological restoration strategies for specific zones. It helps for improve development issues arising from complex interactions between human-environment, facilitating the implementation of restoration practices.